Fome, devoração e os saberes do pé: antropofagia como possibilidade de produção de conhecimento e crítica das desigualdades contemporâneas - Santos, Rafael Renato dos (2022)
The present research focuses on the notion of Anthropophagy developed by Oswald de Andrade from the Anthropophagous Manifesto and the essays, theses, articles and interviews in which he returns to the theme, during his last years of life. With regard to a definition of Anthropophagy, it is possible to verify that there are several meanings linked to it, among which we infer at least three effective connotations: ritual, cultural and philosophical Anthropophagy. It is common to observe in the writings of Oswald and other authors who discussed Anthropophagy the pretension that it could occupy a place of theoretical protagonism and that it could constitute a kind of approach capable of thinking about different aspects of Brazilian society in a critical way. In this sense, the research aims to clarify whether Oswald's claim can be carried out and, advancing in the field of philosophical Anthropophagy, verifies the possibilities of using it as an approach capable of establishing readings on contemporary events and producing knowledge that has as a foundation the critical perspective of social inequalities. The work is based on bibliographic research and is based on the analysis of the notion of Anthropophagy throughout Oswald's works until its delimitation as a philosophical perspective. The results point to the potency of Anthropophagy as a critical stance of Western thought and to the need for further insights into its philosophical nature, considering its counter-hegemonic meaning.